2018
DOI: 10.1016/j.tiv.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparative cytotoxicity study of a novel biocidal iodo-thiocyanate complex

Abstract: Novel biocides, which avoid the induction of cross-resistance to antibiotics, are an urgent societal requirement. Here, we compared the cytotoxic and bactericidal effects of a new antimicrobial agent, the iodo-thiocyanate complex (ITC), with those of the common antiseptics, hydrogen peroxide (HO), povidone iodine (PVP-I) and Lugol's iodine (Lugol). The antimicrobials were co-incubated for 10 min with HeLa and Escherichia coli cells in the presence and absence of organic matter (Dulbecco's modified Eagle's medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…An antimicrobial mouth rinse was devised to take advantage of naturally occurring salivary peroxidases, which contained 4 mM H 2 O 2 and 1 mM KSCN at pH 5.5 . Tonoyan et al described an antibacterial system containing H 2 O 2 , thiocyanate and iodide that produced antibacterial ROS and iodine species under the action of peroxidases . Can selenocyanate improve upon these antimicrobial applications of thiocyanate?…”
Section: Discussionmentioning
confidence: 99%
“…An antimicrobial mouth rinse was devised to take advantage of naturally occurring salivary peroxidases, which contained 4 mM H 2 O 2 and 1 mM KSCN at pH 5.5 . Tonoyan et al described an antibacterial system containing H 2 O 2 , thiocyanate and iodide that produced antibacterial ROS and iodine species under the action of peroxidases . Can selenocyanate improve upon these antimicrobial applications of thiocyanate?…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper described on HeLa cells a beneficial balance between the active concentration and the toxic one for iodine–thiocyanate complexes produced in a non-enzymatic manner, by comparison with other biocide molecules such as hydrogen peroxide. 27 Further studies will have to analyze the interference between this solution of iodine–thiocyanate complexes and the oral microbial ecology. The efficacy of the iodothiocyanate complexes prepared without peroxidase activity has already been demonstrated in vitro on Pseudomonas aeruginosa and on Staphylococcus aureus both in suspension and in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of SCN − at higher concentrations in the saliva should limit the metabolism of I − (oxidation, iodination of tyrosine and iodination of proteins) ( 12 , 62 , 63 ). However, certain studies have suggested a synergy between the two substrates ( 64 ), whereas others have documented the in vitro formation of iodine-SCN − complexes as a more active/stable antimicrobial component, as compared with OI − and OSCN − alone ( 65 68 ).…”
Section: Oral Peroxidases: Enzymes and Substratesmentioning
confidence: 99%